ANALISIS KINERJA KEUANGAN SEBELUM, SAAT DAN SESUDAH COVID-19 PADA EMITEN FARMASI YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Ruzi, Fahrul (Jurnal Profiet, 2024)
This research is aimed at looking at the financial performance of pharmaceutical issuers listed on the Indonesia Stock Exchange before the Covid-19 pandemic, when the pandemic occurred, and after the pandemic. The financial performance observed is the financial performance in 2019, 2020, 2021, 2022 and 2023. The financial ratios observed are ROE, ROE, NPM, CR, DER, INVTO, TATO, and PER. As a result of observations of financial ratios from 2019~2023, it was found that ROE, ROA, NPM, CR, INVTO, TATO, and PER experienced a decreasing trend while DER experienced an increasing trend. Even though there has been an increase in average sales for these pharmaceutical issuers, in terms of financial performance, many have experienced a decline. Keywords: Financial Performance, Financial Ratios, Covid-19